Various Problems And Solutions In Translating Between Arabic And Indonesian - Ghazy Muhyiyuddin Subarkah; Maman Lesmana (International Journal Labs, 2024)
This research examines the challenges and strategies involved in translating Arabic texts, particularly Quranic verses, into Indonesian. Given the significant linguistic and cultural differences between Arabic and Indonesian, translation efforts face numerous obstacles, including issues related to morphology, syntax, semantics, and cultural context. These challenges are compounded by the complexity of translating polysemous words, synonyms, idioms, and metaphors. This research employs qualitative methods, focusing on the translation processes, and offers solutions grounded in established translation techniques. By analyzing selected Quranic verses and creatively crafted Indonesian examples, the research highlights the importance of maintaining grammatical integrity, adapting idioms appropriately, and addressing untranslatability and collocations to ensure that translations are accurate and culturally relevant.